Military deontology and etiquette as the component of professional and moral-aesthetic culture of servicemen of the InteriorTroops of the Ministry of Internal Affairs of Ukraine - Chuprinova, N. Yu. (Honor and Law, 2019)
The article highlights the specificity of military deontology of servicemen of the Interior Troops of the MIA of Ukraine in the system of European deontology codes of law-enforcement personnel ethics and also the etiquette peculiarities of servicemen as the form of professional ethics reflection.